Developing of nanocellulose loaded chitosan-polylactic acid biofilms for green food packaging - Syed, Murtaza Haider; Khan, Maksudur R.; Mior Ahmad Khushairi, Mohd Zahari; Beg, M. D. H.; Norhayati, Abdullah (ICE Publishing, 2024)
The food industry is considered one of the main contributors to plastic waste due to packaging. Sustainable and degradable packaging solutions are the need of the hour. Biopolymers have proved to be a promising replacement for petroleum based polymers. The main reason is their various intrinsic properties like antimicrobial nature and degradability. The main objective of this study was to develop chitosan (CS)/nanocrystalline cellulose (NCC) and polylactic acid (PLA) based biofilms. The biofilms were developed using the drop casting method. The developed biofilms were characterized by SEM, FTIR, XRD, DSC, and thermogravimetric analysis. The performance of the biofilms was checked using mechanical testing, water solubility, porosity, antioxidant, and antibacterial activity. The developed biofilms can solve the issues of environmental pollution being faced by the food packaging industry.